UTILIZATION OF MUSLIM PUBLIC SPACES AS A MEDIUM FOR DISCUSSION OF HALAL FOOD PRODUCTS IN INDONESIA - Mella Azizah (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2024)
Public space is formed from the development of communication and information ztechnology involving internet users in cyberspace. Public space is utilized as a forum for discussion related to halal food products in Indonesia by the Muslim community. This discussion related to Muslim public space uses a case study method to examine phenomena that exist on Instagram social media. The discussion results show that mass media can be used effectively to exchange information between individuals included in the cyber community to discuss various aspects of halal food products in Indonesia. The role of public space as a forum for discussion of halal food products can add insight and improve the quality of consumers in choosing halal food products.